Pengaruh Etos Kerja, Kompensasi Finansial dan Budaya Tri Hita Karana terhadap Kinerja - Ariawan, I Komang; Ayu Yayati Wilyadewi, Ida I Dewa; Purwaningrat, Putu Atim (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
The purpose of this study was to find out how the work ethic, financial compensation and culture of tri hita karana affect employee performance either partially or simultaneously. This research was conducted at PT. Cahaya Surya Bali Indah. The number of samples taken were 48 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. While the data analysis techniques are validity, reliability, classical assumption test, multiple linear regression analysis, multiple correlation, t test (t test), determination, and f test (f test). The test results show that work ethic has a positive and significant effect on employee performance at PT. Cahaya Surya Bali Indah. Financial compensation has a positive and significant effect on employee performance at PT. Cahaya Surya Bali Indah. Tri hita karana culture has a positive and significant effect on employee performance at PT. Cahaya Surya Bali Indah. Organizational culture, financial compensation and culture tri hita karana simultaneously have a positive and significant effect on employee performance at PT PT. Cahaya Surya Bali Indah.